Integration of Independent Learning Curriculum in Islamic Religious Education Towards the Era of Society 5.0 - Ihsan, Muhammad; Sukino, Sukino; Usman, Usman (Arfannur, 2024)
This research is driven by the need for innovative media use in Islamic Education to enhance student engagement in the Society 5.0 era. The Indonesian government's introduction of a revolutionary autonomous learning curriculum reflects the educational demands of this era, closely linked to 21st-century skills. This necessitates advanced and adaptable teaching concepts and methods, requiring continuous development across all school aspects, particularly in Islamic Education. The study aims to explore how Islamic Education courses can effectively integrate the autonomous learning curriculum in preparation for Society 5.0. A library research method was utilized alongside a qualitative naturalistic paradigm approach. Findings indicate that incorporating self-directed learning into the curriculum aligns with the characteristics of Society 5.0. To develop resilient, skilled, and dedicated human resources, creativity and innovation are essential. Thorough preparation is crucial for successfully integrating Islamic Education into the autonomous learning curriculum, which will elevate educational standards in Indonesia and produce morally upright and intelligent students.